ANALISIS ANTRIAN ANGKUTAN BARANG PADA JEMBATAN TIMBANG DENGAN METODE SIMULASI MULTIPLE CHANNEL (STUDI KASUS PADA JEMBATAN TIMBANG SARANG) - Nicolas Ananto Seno W.; Muhammad Arsyad Sulistiono; Bambang Riyanto; Kami Hari Basuki (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Sarang Weighbridge is one of the busy weighbridge that serve freight vehicles in the province of Central Java. With the large number of vehicles to be serviced will cause potential queues at the weighbridge. This study aims to determine the pattern of queues that occur at weigh stations and provide a recommendation to the appropriate queue system to be applicable to the Sarang Weighbridge, so it can increased the performance of the weighbridge.The method used to analyze queues in this study is the simulation method. This method is used because there are many variables at Weighbridge queuing system so it will be very difficult when using the methods of mathematical analysis. Simulation begins with field survey data. The data is used to perform the simulation and the results are then tested for compliance with the Poisson distribution . From the simulation results will then be made a better queuing models. Based on the analysis that we did, needed a better queuing system and the need to improve the infrastructure and human resources in order to better service on Sarang Weighbridge